Новые клещи-фитосейиды Крыма (Parasitiformes, Phytoseiidae). Сообщение II - Колодочка, Л.А. (Вестник зоологии, 1981)
The data are presented on the habitat of 17 species of Phytoseiidaemites whichare first found in the Crimea. Description and drawings of the species Ambluseius plantagenis sp. n. are given.